Nothing Is Not One: Revisiting the ex nihilo. (25th March 2013) - Burrus, Virginia
Abstract This article seeks to encounter the late ancient doctrine of creatio ex nihilo from a new angle, gently questioning both its distinctive Christianness and its inevitable alignment with a theology of absolute sovereignty. Franz Rosenzweig's idiosyncratic elaboration of this doctrine opens up new lines of thought: multiplying the "nothing" while also emphasizing its fecundity, he articulates not only a negative theology but also a negative anthropology and cosmology; insisting on the irreducible relationality of God, human, and world, he also posits their non‐essentiality. Admittedly, early versions of creatio ex nihilo (Irenaeus, Tertullian) foreground the omnipotence of the creator and the goodness of the created world, and these concerns continue to be expressed by later proponents of the ex nihilo, Jewish as well as Christian. However, beginning in the fourth century there are hints of something new as well, something more Rosenzweigian—namely, a preoccupation with the nothing itself. What comes increasingly to the fore in these articulations of the ex nihilo is not mastery but mystery, not power but fragility, not separation but intimacy—and paradoxically so, given that the gap between creator and created has never before seemed to yawn so widely. This shift is manifest in the opening passages of Genesis Rabbah, I would suggest. It is also evident in the locus classicus of post‐Constantinian Christian ex nihilo doctrine, namely Athanasius's On the Incarnation of the Word of God.